Smart stimuli-responsive injectable gels and hydrogels for drug delivery and tissue engineering applications: A review - Salehi, Saba; Naghib, Seyed Morteza; Garshasbi, Hamid Reza; Ghorbanzadeh, Sadegh; Zhang, Wei (Frontiers in Bioengineering and Biotechnology, 2023)
Hydrogels are widely used biomaterials in the delivery of therapeutic agents, including drugs, genes, proteins, etc., as well as tissue engineering, due to obvious properties such as biocompatibility and their similarity to natural body tissues. Some of these substances have the feature of injectability, which means that the substance is injected into the desired place in the solution state and then turns into the gel, which makes it possible to administer them from a way with a minimal amount of invasion and eliminate the need for surgery to implant pre-formed materials. Gelation can be caused by a stimulus and/or spontaneously. Suppose this induces due to the effect of one or many stimuli. In that case, the material in question is called stimuli-responsive because it responds to the surrounding conditions. In this context, we introduce the different stimuli that cause gelation and investigate the different mechanisms of the transformation of the solution into the gel in them. Also, we study special structures, such as nano gels or nanocomposite gels.